Pengaruh Profitabilitas Dan Kepemilikan Asing Terhadap Nilaiperusahaan Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Periode 2016 - 2020 - Maulana Habibullah (Manajemen Kreatif Jurnal, 2023)
Maulana Habibullah Nim:17230027, S1-Accounting Department, 2022, The Effect of Profitability and Foreign Ownership on Firm Value in Manufacturing Companies on the Indonesia Evek Stock Exchange for the 2016-2020 period. This study aims to determine the Effect of Profitability and Foreign Ownership on Firm Value and this study aims to determine how much influence. Methods of data collection through questionnaires and literature study. The analytical method used is multiple regression analysis. The sample technique used was purposive sampling of 27 companies. The research results obtained based on the partial test (t test) obtained: Based on the results of the first hypothesis testing partially Profitability proxied by Return on Assets has a significant effect on company value in manufacturing companies listed on the Indonesian stock exchange Based on the results of testing the second hypothesis partially Profitability proxied by Return on Equity has no effect on firm value in manufacturing companies listed on the Indonesian stock exchange Based on the results of testing the third hypothesis partially, foreign ownership has a significant effect on firm value in manufacturing companies listed on the Indonesian Stock Exchange Based on the results of hypothesis testing fourthly simultaneously Profitability proxied by ROA and ROE as well as foreign ownership jointly has a positive and significant effect on company value in manufacturing companies listed on the Indonesian stock exchange.